(untitled) (Brazilian Journal of Radiation Sciences, 2018)
Computed Tomography (CT) has become an important tool to diagnose cancer and to obtain additional information for different clinical questions. However, CT scan usually requires a higher radiation exposure than a conventional radiography examination. Head CT scans are used for diagnosis of traumatic head injuries, infections and other diseases with instability. Based on this information, it was studied the dose variation deposited in the lenses and in nearby organs, such as: pharynx, hypophysis and salivary gland with and without the use of bismuth shield. In this study a head CT scan was performed on anthropomorphic male phantom using a GE scanner. Dose measurements have been performed by using radiochromic film strips to register the individual doses in the organs of interest. The results show us that the lenses had a reduction of 26% of the dose with the use of the bismuth shield.